The Effects of Climate Change on Variability of the Growing Seasons in the Elbe River Lowland, Czech Republic - Vera Potopová; Pavel Zahradníček; Luboš Türkott; Petr Štěpánek; Josef Soukup (Advances in Meteorology)
This research aimed to identify an approach for adaptation of agriculture to increased climate variability and projected changes, taking into account regional specificity of climate change. Changes in the timing of growing season (GS) parameters for both observation and models data were computed using daily mean temperatures for three thresholds that correspond to the physiological requirements of the vegetable types. This research included a new assessment of the potential impacts of climate change on the GS of vegetables grown in the Elbe River lowland, one of the largest farmed vegetable regions in Central Europe. To accomplish this, a comprehensive analysis was conducted of the spatiotemporal variability of the date of the beginning of the growing season (BGS), the date of the end of the growing season (EGS), and the length of the growing season (GSL) for the period 1961–2011. In addition, an assessment was made of the potential changes in the dates of the BGS, EGS, and GSL for the Elbe River lowland, simulated using the regional climate models. Prospective areas for growing thermophilic vegetables in the study region were also determined.